Cries from the Cross: Jesus and the Wrongfully Convicted - Trinka, Luke (Lumen et Vita, 2021)
This paper endeavors to affirm the humanity, make known the pain, and lift up the prophetic witness of wrongfully convicted individuals. I bring forward their spiritual journeys and place them in dialectical relationship with Jesus Christ. When we understand Jesus’ death as utterly wrongful and position him in radical solidarity with the wrongly condemned, we see that when the State wrongfully incarcerates, cages, and executes, Jesus too is crucified.